ICSA bulletin : . Bulletin of the Continuation Committee of the World Conference against Apartheid, Racism and Colonialism in Southern Africa
Till (1978):no.2 titled: Bulletin of the Continuation Committee of the World Conference against Apartheid, Racism and Colonialism in Southern Africa.